Pengaruh Motivasi Intrinsik Dan Motivasi Ekstrinsik Terhadap Kinerja Karyawan Pada CV. Riho Mandiri - Restu Hayati; Desy Mardianty; Lintang Nur Agia; Prasetia Denny (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine and analyze the effect of intrinsic motivation and extrinsic motivation on employee performance at CV. Ridho Mandiri. The population of this research is all employees who work in this business entity. The sampling technique in this study uses the cencus method (total sampling) which is a sampling technique where all members of the population are sampled, amounting to 30 people. Data collection techniques in this study were questionnaires, interviews and documentation. The data analysis technique in this study uses confirmatory factor analysis (CFA) SmartPLS 3. This study's results indicate that intrinsic and extrinsic motivation partially and simultaneously affect employee performance at CV. Ridho Mandiri.